Impact of obesity on follicular fluid lipid composition and IVF/ICSI outcomes in Korean women: A lipidomic study - Yoo Ra Ko; Min Kyoung Kim; Ji Won Kim; E. Jung Han; Se Jeong Kim; Jae Kyun Park; So Yeon Ahn; Minseo Lee; Surim Oh; Sohyun Hwang; Donghyeon Kim; Hyunjung Jade Lim; et al. (PLoS ONE, 2025)
Background Obesity negatively affects reproduction and in vitro fertilization (IVF) outcomes. However, its effects on lipid metabolism during embryonic development remain unclear. We examined follicular fluid (FF) lipid composition and body mass index (BMI)-related embryological outcomes in Korean women undergoing IVF/intracytoplasmic sperm injection (ICSI). Methods This prospective cohort study included 68 Korean women with infertility without metabolic diseases who underwent IVF/ICSI. Patients were categorized according to the 2022 guidelines of the Korean Society for the Study of Obesity as follows: Group A (obese, BMI ≥ 25 kg/m2, n = 28) and Group B (non-obese, BMI < 25 kg/m2, n = 40). Liquid chromatography-tandem mass spectrometry (LC-MS) was used to analyze lipids in the FF. Principal component analysis (PCA) and correlation analyses were performed. Embryological outcomes according to the BMI were compared using the QUADE nonparametric analysis of covariance adjusted for age and anti-Müllerian hormone. Results LC-MS identified 159 of the 230 lipids in the FF samples. Diacylglycerol (DAG), triacylglycerol (TAG), and acylcarnitine (AC) levels were significantly higher in the obese group; whereas monoacylglycerol (MAG) and plasmenyl phosphatidylcholine levels were lower. PCA explained 38.9% of the variance between the groups. Significant inter-group differences were found in the DAG (adjusted p < 0.05) and AC 16:1 (adjusted p = 0.0139) levels. BMI and TAG, DAG, and AC levels (adjusted p < 0.05) were positively correlated. Obese group had fewer fertilized oocytes (5.07 ± 4.16 vs. 6.65 ± 4.61, p = 0.043), cleavage-stage embryos (4.86 ± 4.26 vs. 6.63 ± 4.61, p = 0.016), and morula-stage embryos (4.00 ± 4.51 vs. 6.05 ± 5.14, p = 0.024). Conclusions Obesity alters FF lipid composition in women with infertility undergoing IVF/ICSI, potentially affecting early embryonic development. This study improves our understanding of its effects on the ovarian microenvironment and offers insights into targeted IVF interventions.